2018
DOI: 10.25100/iyc.v20i2.5809
|View full text |Cite
|
Sign up to set email alerts
|

Efecto De Las Condiciones Del Hidrosecado Sobre El Encogimiento De Trozos De Zapallo (Cucurbita Maxima)

Abstract: El método para secar apropiadamente frutas y vegetales debe incrementar la calidad del producto terminado además de ser económicamente viable, por tal motivo, se han aplicado y desarrollado varias tecnologías que incluyen pre-tratamientos y mejoras a la técnica de secado misma. Mediante la metodología para muestras gruesas llamada “hidrosecado conductivo” basada en la técnica de Ventana de Refractancia (RWTM), se deshidrataron trozos rectangulares de zapallo (1.2 x 1.1 x 5.9 cm3)  usando un baño termostático c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Regarding the drying of fruits and vegetables with RW, only 26 studies were found by the Web of Science tool in the last 10 years, studying: apple (Hernández et al, 2020;Nascimento et al, 2020;Rajoriya et al, 2019Rajoriya et al, , 2020; mango (Shende & Datta, 2020;Zotarelli et al, 2015); papaya (Minuye et al, 2021); yam (Santos et al, 2020); beetroot (Preethi et al, 2020); physalis (Puente-Díaz et al, 2020); sapota (Jalgaonkar et al, 2020); pomegranate (Baeghbali et al, 2016;Tontul & Topuz, 2019); pupunha, tucupi and mango (Costa et al, 2019); cherry, blueberry and strawberry (Nemzer et al, 2018;Tontul et al, 2018); guava (Frabetti et al, 2018;Leiton-Ramírez et al, 2020b), and pumpkin (Ortiz & Ochoa-Martínez, 2018).…”
Section: Refractance Window (Rw)mentioning
confidence: 99%
“…Regarding the drying of fruits and vegetables with RW, only 26 studies were found by the Web of Science tool in the last 10 years, studying: apple (Hernández et al, 2020;Nascimento et al, 2020;Rajoriya et al, 2019Rajoriya et al, , 2020; mango (Shende & Datta, 2020;Zotarelli et al, 2015); papaya (Minuye et al, 2021); yam (Santos et al, 2020); beetroot (Preethi et al, 2020); physalis (Puente-Díaz et al, 2020); sapota (Jalgaonkar et al, 2020); pomegranate (Baeghbali et al, 2016;Tontul & Topuz, 2019); pupunha, tucupi and mango (Costa et al, 2019); cherry, blueberry and strawberry (Nemzer et al, 2018;Tontul et al, 2018); guava (Frabetti et al, 2018;Leiton-Ramírez et al, 2020b), and pumpkin (Ortiz & Ochoa-Martínez, 2018).…”
Section: Refractance Window (Rw)mentioning
confidence: 99%
“…From the above, it is important to clarify that heat transfer through radiation is significant when the thickness of the fruit puree layer is small (1 mm); when its thickness is high, heat transfer occurs with a more significant contribution by conduction due to the additional thickness of solid [78]. Thus, the transfer of thermal energy from hot water to the fruit layer can occur predominantly through radiation and conduction mechanisms [62].…”
mentioning
confidence: 99%